The use of minoxidil in diseases associated with hair loss - Alina Graczyk; Anna Waśkiel-Burnat; Adriana Rakowska; Lidia Rudnicka (Przegląd Dermatologiczny, 2023)
Minoxidil is a drug with a hypotensive effect. It was introduced in the 1970s in the treatment of hypertension. This drug is characterized by a multifaceted mechanism of action – including a vasodilatory effect, probably through the activation of the ATP-sensitive potassium channels in vascular smooth muscle cells. Hypertrichosis was observed in patients treated with minoxidil, which prompted research into the possibility of applying this drug to diseases associated with alopecia. The first attempts were unsuccessful due to side effects associated with its hypotensive effect. Introduction of local treatment, and in recent years also methods of oral treatment with low doses of minoxidil, has allowed it to achieve a good therapeutic effect without a significant risk of side effects. In dermatology, the effect of minoxidil associated with stimulation of the onset and prolongation of the anagen phase is used. Minoxidil is available in the form of 2% and 5% solutions, 5% foam and in the form of compound drug for either topical or oral treatment. Side effects are present in 15–20% of patients and in most cases, they do not lead to discontinuation of the treatment. The most common side effects of topical preparations include itching, erythema, and scaling, while in the oral form, hypertrichosis of the facial skin, dizziness, and swelling of the lower limbs are most often observed.